MAGNETIC CATACLYSMIC VARIABLES: 25 YEARS OF EXCITING PERFOMANCE - Andronov, I. L (Одеські астрономічні публікації, 2017)
Exactly 25 years ago, Santiago Tapia has detected circular and linear polarization of AM Her varying with the same period as the photometric and spectral characteristics. This had lead to a discovery of unprecedentedly exotic binary systems, in which the strength of the magnetic field is large enough to keep the white dwarf in a synchronism, dominating the accretion torque. Nowadays, about 70 representatives of this class of polars have been registered. We review the history of study of polars, starting with a "standard model", according to which, the red dwarf fills its Roche lobe and the is captured and channelized by a magnetic field of the white dwarf in the vicinities of the inner Lagrangian point. The models of the "propeller", "idling", "magnetic valve", "swinging dipole", "boiling asymmetric rainbow column" are reviewed, with a special attention to the unsolved problems of this study - contradiction between the observed synchronism of spin and orbital periods of the white dwarf with a possible presence of the partially ballistic trajectory of the accretion and possibly important contributions of the dipole and multipole components of the magnetic fields; presence of few mechanisms of luminosity variations; various types and mechanisms of variability at different time scales from seconds to decades. The monitoring of AM Her (and later on other objects) has started inOdessain 1978 and was regularly continued in the Crimean Astrophysical observatory since 1989. The results will be published in the "Atlas and catalogue of the polarimetric and photometric characteristics" by N.M.Shakhovskoy, I.L.Andronov and S.V.Kolesnikov. Other papers absent in the ADS are available via http://il-a.pochtamt.ru or www.paco.odessa.ua/~il-a. Despite 25 years have passed, these stars still exhibit new observational surprizes challenging theoretical models.